2019
DOI: 10.1017/s1751731118002318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromium supplementation on growth performance, meal pattern, metabolic and antioxidant status and insulin sensitivity of summer-exposed weaned dairy calves

Abstract: Stressful situations may result in serum chromium (Cr) depletion with increased urinary excretion of the mineral and increased Cr requirements. The objective of this study was to investigate the effects of Cr supplementation on growth performance, feeding behavior, blood metabolites and hormones, indicators of oxidative stress and glucose-insulin kinetics of summer-exposed weaned dairy calves. In total, 48 Holstein female calves (63 days of age; 77.0±1.45 kg of BW) were assigned randomly to one of two treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
5
2
0
1
Order By: Relevance
“…In line with Kargar et al (2018a,b) and Mousavi et al (2019a), the present study showed that blood levels of glucose, insulin, insulin: glucose ratio, T 3 , T 4 , or T 3 :T 4 ratio were not influenced by Cr supplementation. In line with the present findings, Cr supplementation increased blood levels of cortisol in heat-stressed calves (Yari et al, 2010).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…In line with Kargar et al (2018a,b) and Mousavi et al (2019a), the present study showed that blood levels of glucose, insulin, insulin: glucose ratio, T 3 , T 4 , or T 3 :T 4 ratio were not influenced by Cr supplementation. In line with the present findings, Cr supplementation increased blood levels of cortisol in heat-stressed calves (Yari et al, 2010).…”
supporting
confidence: 93%
“…There are reports in growing dairy heifers indicating that Cr supplementation may increase glucose disposal rate or decrease T 1/2 (Jovanović et al, 2017;Mousavi et al, 2019b) or decrease insulin release or AUC (Yari et al, 2010;Spears et al, 2012). In the present trial, glucose kinetics data were not affected by supplementing Cr, which is in line with previous reports by Mousavi et al (2019a), who supplemented 0.05 mg of Cr-Met/kg of BW to dairy calves after weaning. In a trial by Yari et al (2010), Cr-Met supplementation decreased insulin AUC following glucose infusion without affecting glucose AUC.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Chromium methionine (CrMet), in particular, has been considered one of the best options for protecting the increased IMF content from oxidation . However, studies on the antioxidant effect of CrMet have mainly focused on mammals . Furthermore, diets supplemented with CrMet increased the muscle marbling score and PUFA contents, improving meat quality in steers .…”
Section: Introductionmentioning
confidence: 99%